A case study on the adoption of cloud computing in Malaysia from the perspectives of cloud providers - Mohamad Puad, Noor Hazwani; Md Ali, Asma; Suhaimi, Mohd Adam; Hussin, Husnayati (School of Industrial and System Engineering, Telkom University, Indonesia, 2019)
The objective of this study is to discover the perspectives of cloud providers towards cloud computing adoption in Malaysia in terms of the challenges faced them. Data were collected through semi-structured interviews with three cloud providers. The findings indicated security concern, difficulties in learning the cloud computing infrastructure, changes in IT roles, high cost of bandwidth and lifespan of IT equipment as challenges faced by cloud providers in providing cloud service in Malaysia. This study helps people to understand more about the current issues in cloud computing adoption in Malaysia from the perspectives of cloud provider and at the same time provide support to Industry 4.0.